Room Reservation System (RRS) for Hotel UiTM Dungun /Nurul Diana Roslan - Roslan, Nurul Diana (2014)
Online room reservation systems for hotel are increasing in importance and greatly facilitate cross-border consumer activity. The Internet has enabled hotels to contract directly with a huge number of potential customers. This report describes implementation of Room Reservation system (RRS) for Hotel UiTM Dungun. Based on the interview with the supervisor of Hotel UiTM Dungun, and observation of the current reservation process at Hotel UiTM Dungun, several problems are identified. The hotel is still using the manual forms for reservation process and the guest’s information are stored in Microsoft Office Excel file. Other than that, hotels’ staffs are facing with problem in handling and managing mass of information. To overcome this problem, Room Reservation System (RRS) is developed to helps people to make a room reservation easily through online. Aside from that, the hotel management can easily manage with mass of information more systematic and efficient by using RRS. RRS is developed based on phases in the Waterfall Model which are Planning, Analysis, Design, Implementation and Documentation. In evaluating this system, the quantitative data analysis was conducted to evaluate the user interfaces and usability of RRS. The data findings were assembled through the questionnaire survey with 30 respondents. There are 5 factors that need to be evaluated which are user interfaces, usefulness, ease of use, ease of learning and satisfaction. The findings indicate that about 57% to 67% of the 30 respondents strongly agreed that RRS is usefulness, easy to use, easy to learn, achieve the satisfaction and the user interfaces are suitable for RRS